1981
DOI: 10.1080/15287398109530069
|View full text |Cite
|
Sign up to set email alerts
|

Trace element levels in tissues from cattle fed a sewage sludge‐amended diet

Abstract: The levels of 20 elements (Al, Ca, Cd, Cl, Co, Cu, Fe, K, Mg, Mn, Mo, Na, Ni, P, Pb, Rb, Sb, Se, V, and Zn) are reported for kidney, liver, muscle, spleen, and brain tissues taken from two groups of six steers per group in a feeding study conducted at Colorado State University. The control group was fed a normal feedlot cattle ration and the test group was fed the same ration amended with 12% (by weight) air-dried municipal sewage sludge. Elemental levels are also reported for the control and test diets, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Although metals in the tissues of animals have been studied for many years, it was not possible to source or gain access to a standard reference set of metals in cattle or sheep to compare with this study. Those publications we could access (e.g., Boyer et al, 1981;Erdogan et al, 2004;Miranda et al, 2006) provided only limited information on small number of animals but largely correlated well with our findings.…”
Section: Discussionsupporting
confidence: 86%
“…Although metals in the tissues of animals have been studied for many years, it was not possible to source or gain access to a standard reference set of metals in cattle or sheep to compare with this study. Those publications we could access (e.g., Boyer et al, 1981;Erdogan et al, 2004;Miranda et al, 2006) provided only limited information on small number of animals but largely correlated well with our findings.…”
Section: Discussionsupporting
confidence: 86%
“…The current study reports that an adequate vitamin D status is associated with higher BMD and the association of vitamin A with BMD appears to vary by vitamin D status in men. We cannot overlook a possibility of bias evaluating the vitamin A intake through, for example, milk [ 31 ], butter [ 32 ] and liver [ 33 , 34 ], since these foods can be related with low bone mass or osteoporosis risk due to an environmental toxin or other negative effect on bone. In addition, there is a potential for misclassification of vitamin A intake assessed by a 24-hour dietary recall questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…The higher value (1.2 Â 10 À3 d kg À1 ) in Table 4 is based upon two continuous feeding studies reported by Sirotkin et al (1970) and Sirotkin (1987) although the animals were either six months old or slightly younger. The latter value appears reasonable compared with the concentration ratio value (IAEA, in press), which can be estimated from Boyer et al (1981).…”
Section: Beefmentioning
confidence: 95%